Flexible budgeting is a tool for planning and controlling indirect industrial costs-an applied study at Al-Furat Chemical Industries Company - فائز نعيم يوسف; حسين عمران ناجي (Iraqi Journal for Administrative Sciences, 2024)
Planning and controlling are considered two of the important functions management firms try to practice to avoid waste and extravagance and achieve the best exploitation for the potential sources and energies, then measure the performance and achieve responsibility accounting. This should all be carried out in a scientific way represented by balances. The study aims to show the effect of a flexible budget on both planning and controlling indirect industrial costs the way of preparing it and how it differs from a stable budget flexible budget is prepared for a number of the expected levels of activities within the appropriate range instead of one level of activity. It also facilitates the process of measuring performance through preparing a budget for the real achieved level of activity and comparing it with the real performance to illicit the deviations analyzing them, knowing their reasons treating them, and setting the necessary procedures for not doing them again. Such a comparison is useful for companies with the same level of activity. A stable budget is prepared for one level of activity and when the real level of activity is changed from its planned level activity. The performance measurement process will be incorrect for it compares two different activities, and hence the importance of a flexible budget becomes clear in both planning and controlling.